1990
DOI: 10.1177/089686089001000212
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter Jejuni Peritonitis During Chronic Ambulatory Peritoneal Dialysis (CAPD)

Abstract: A patient treated with chronic ambulatory peritoneal dialysis developed recurrent peritonitis. During a fourth episode, Campylobacter jejuni was cultured from the dialysate. She responded well to streptokinase and imipenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Moreover, Campylobacter jejuni II, isolated from dialysate effluent, was resistant in vitro to cephalosporins and vancomycin, which the patient received only once on the day of hospital admission. This observation is in agreement with data in literature concerning experience with intravenous erythromycin as an effective treatment for Campylobacter jejuni peritonitis (2). Although oral erythromycin has been discussed as an additional treatment in some articles (3,4), cure of Campy-lobacter peritonitis due to monotherapy with oral CLA has never been reported.…”
supporting
confidence: 90%
“…Moreover, Campylobacter jejuni II, isolated from dialysate effluent, was resistant in vitro to cephalosporins and vancomycin, which the patient received only once on the day of hospital admission. This observation is in agreement with data in literature concerning experience with intravenous erythromycin as an effective treatment for Campylobacter jejuni peritonitis (2). Although oral erythromycin has been discussed as an additional treatment in some articles (3,4), cure of Campy-lobacter peritonitis due to monotherapy with oral CLA has never been reported.…”
supporting
confidence: 90%
“…To our knowledge, there have been only 16 reports of peritonitis caused by C. jejuni (including the present case), 3 of which were accompanied by bacteremia by an indistinguishable organism (Table 1) (3,6-14). The patients in these reports were aged between 30 and 75 years, with a male-to-female ratio of 1.…”
Section: Discussionmentioning
confidence: 77%
“…In other words, we observed a much less favorable response of Campylobacter peritonitis to cefazolin than was reported by Elshafie et al (9), whose 3 cases of Campylobacter peritonitis were all susceptible to cefazolin (9). Earlier studies have reported effective regimes including cefazolin (9), erythromycin plus tobramycin (13), clarithromycin (14), imipenem (15), meropenem (16), gentamicin plus ciprofloxacin (17), vancomycin plus norfloxacin (18), vancomycin plus netilmicin and ciprofloxacin (19), and vancomycin plus gentamicin (20). Interestingly, all 6 patients who failed to respond by day 5 in our series (Table 3) improved after administration of an oral macrolide (erythromycin or clarithromycin); 5 achieved a complete cure, and 1 patient experienced relapse of culture-negative peritonitis.…”
Section: Discussionmentioning
confidence: 99%